3D printed magnesium silicate/β-tricalcium phosphate scaffolds promote coupled osteogenesis and angiogenesis - Wang, Lulu; Shen, Mingkui; Tang, Zhongxin; Tan, Jun; Li, Kuankuan; Ma, Haijun (Frontiers in Bioengineering and Biotechnology, 2025)
Fabricating bone tissue engineering substitutes with functional activity remains a challenge for bone defect repair requiring coordinated coupling between osteogenesis and angiogenesis. In this research, we evaluated and analyzed magnesium silicate/β-Tricalcium phosphate (MS/β-TCP) scaffold on angiogenesis and bone regeneration in vitro and in vivo, and the mechanism of its action were described. Achieving magnesium and silicon ions sustained release, 3D printed MS/β-TCP scaffolds possessed appropriate mechanical properties and had excellent biocompatibility that was suitable for osteoblastic MC3T3-E1 cells and human umbilical vein endothelial cells (HUVECs) with proliferation, adhesion, and migration. Combined techniques of Transwell co-culture, we studied the effect of MS/β-TCP scaffold activated cell-level specific regulatory network, which promotes the osteogenic differentiation of MC3T3-E1 and the endothelial formation of HUVEC by significantly up-regulating the expression of related genes and proteins. In addition, RNA sequencing (RNA-seq) revealed MS/β-TCP scaffold plays a dual role in osteogenesis and angiogenesis by activating PI3K/Akt signal pathway, whereas the expression of genes and proteins associated with osteogenesis and angiogenesis was significantly downregulated the PI3K/Akt signaling pathway was inhibited. Additionally, in vivo studies showed that MS/β-TCP scaffolds increased the growth of vascular and promoted the bone regeneration at the bone defect sites in rats. In summary, 3D printed MS/β-TCP scaffolds with effectively osteogenic and angiogenic induction will be an ideal bone substitute applied in bone defect repair for clinical application in the future.